2022
DOI: 10.4103/ijmr.ijmr_808_18
|View full text |Cite|
|
Sign up to set email alerts
|

Urinary immunoglobulins in viral diagnosis: An overview

Abstract: Antibody detection by serological methods gained a lot of interest in recent years and has become the backbone of virological diagnosis. Despite the detection of all five classes of immunoglobulins in urine, not much attention has been paid to the use of urine as a diagnostic sample to detect viral antibodies. Unlike venipuncture, this non-invasive mode of sample collection can help cover all age groups, especially paediatric and old age patients, where blood collection is difficult. Using urine as a sample is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…However, the impact of such buffers on the stability and integrity of IgG in FVU, has not been explored. Furthermore, while studies have demonstrated urinary IgG stability under various conditions for specific viral pathogens 16 , 17 , a knowledge gap exists regarding the stability of (HPV-specific) IgG in FVU.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the impact of such buffers on the stability and integrity of IgG in FVU, has not been explored. Furthermore, while studies have demonstrated urinary IgG stability under various conditions for specific viral pathogens 16 , 17 , a knowledge gap exists regarding the stability of (HPV-specific) IgG in FVU.…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of such buffers on the stability and integrity of IgG in FVU, has not been explored. Furthermore, while studies have demonstrated urinary IgG stability under various conditions for specific viral pathogens 16,17 , a knowledge gap exists regarding the stability of (HPV-specific) IgG in FVU.Earlier studies showed that FVU contains limited quantities of IgG, approximately 0.5% of total IgG and 0.07% of HPV-specific IgG compared to serum levels 18 . While these studies have demonstrated good correlations between serum and FVU HPV-specific antibodies, FVU samples still exhibit lower antibody positivity…”
mentioning
confidence: 99%
“…Recently, as a novel approach, the effectiveness of anonymous vending machine-based urine self-collection for HIV testing programs was assessed among college students across China and was shown to be a powerful tool to promote HIV testing [ 34 ]. The US Food and Drug Administration (US-FDA) licensed an enzyme immunoassay for the detection of HIV-1 antibodies in urine in 2019 [ 35 ] and advocates for urine in the screening of high-risk populations as the reports show that screening urine could serve as an improved alternative to oral specimens [ 36 ]. Akin to oral fluid-based HIV-ST, urine can also be disposed of safely after use.…”
Section: Introductionmentioning
confidence: 99%